Enhancing self-efficacy improves episodic future thinking and social-decision making in combat veterans with posttraumatic stress disorder. (30th August 2016) - Brown, Adam D.; Kouri, Nicole A.; Rahman, Nadia; Joscelyne, Amy; Bryant, Richard A.; Marmar, Charles R.
Abstract: Posttraumatic Stress Disorder (PTSD) is associated with maladaptive changes in self-identity, including impoverished perceived self-efficacy. This study examined if enhancing perceptions of self-efficacy in combat veterans with and without symptoms of PTSD promotes cognitive strategies associated with positive mental health outcomes. Prior to completing a future thinking and social problem-solving task, sixty-two OEF/OIF veterans with and without symptoms of PTSD were randomized to either a high self-efficacy (HSE) induction in which they were asked to recall three autobiographical memories demonstrating self-efficacy or a control condition in which they recalled any three autobiographical events. An interaction between HSE and PTSD revealed that individuals with symptoms of PTSD in the HSE condition generated future events with more self-efficacious statements than those with PTSD in the control condition, whereas those without PTSD did not differ in self-efficacy content across the conditions. In addition, individuals in the HSE condition exhibited better social problem solving than those in the control condition. Increasing perceptions of self-efficacy may promote future thinking and problem solving in ways that are relevant to overcoming trauma and adversity. Highlights: Implemented novel induction to increase perceptions of self-efficacy in individuals with PTSD. Induction led to greater self-efficacy content on future thinking task in individuals with PTSD. Induction led to better performance on social-problem solving task. Use of self-efficacy autobiographical memories may aid in the treatment of PTSD.